The most common problems and challenges in conducting business web surveys - Žmuk, Berislav (Oeconomica Jadertina, 2019)
Conducting business surveys can lead to very important information about companies’ views on a particular topic, as well as problems that prevent companies from achieving plans and accomplish a higher level of business success. With the development of information and communication technologies and the increasing number of users who successfully apply these technologies in their daily work, web surveys have become the most efficient means of gathering information from a large number of companies. However, conducting business web surveys is not as simple as it might seem at first glance. Therefore, the paper gives an overview of the most important challenges of successfully conducting business web surveys. Challenges that are particularly highlighted and addressed in the paper are related to: the target population and the framework of unit selection in the sample; the reporting unit and the credibility of the response; questionnaire design and technical aspects of the web survey; sending invitations to participate in research and reminders and duration of research; low response rates; analysis of the information collected and interpretation of the results obtained; and feedback from companies.